Kick the Cat: A Serial Crossover Effect of Supervisors’ Ego Depletion on Subordinates’ Deviant Behavior - Ming, Xiaodong; Bai, Xinwen; Lin, Lin (Frontiers in Psychology, 2020)
Drawing on the crossover model and conservation of resources theory, we explore the mechanism through which supervisors’ ego depletion induces subordinates’ deviant behavior. Using the two-wave survey data from 24 supervisors and their 192 respective subordinates, we found supports for our hypotheses that (a) abusive supervision mediated the effect of supervisors’ ego depletion on subordinates’ ego depletion; (b) subordinates’ ego depletion mediated the effect of abusive supervision on subordinates’ deviant behavior; and (c) abusive supervision and subordinates’ ego depletion serially mediated the effect of supervisors’ ego depletion on subordinates’ deviant behavior. Our serial crossover model posits that both ego depletion and unethical behavior can be transmitted from supervisors to subordinates, and that these two crossover processes are entwined with each other. Findings are discussed in terms of theoretical contributions and practical implications.